1997
DOI: 10.1046/j.1365-2885.1997.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of penicillin‐G in ewes and cows in late pregnancy and in early lactation

Abstract: Concentrations of penicillin-G in serum were determined after single intravenous doses of potassium penicillin-G (10 mg/kg body wt) to ewes and cows in late pregnancy and in early lactation. Penicillin-G in serum was analysed by a microbiological method and pharmacokinetic parameters were calculated by model-independent methods. Serum concentrations were lower in early lactation than in late pregnancy in both ewes and cows. The differences were statistically significant at most sampling times in ewes but only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 11 publications
3
21
1
Order By: Relevance
“…Ranheim et al reported that the clearance of penicillin was lower in 1-week-old piglets than in adult pigs (7,51). Musser et al found that the volume of distribution at steady state (V ss ) of the calf was significantly higher than that of adult cattle (5,30). The use of adult data only may not be able to describe all of the PK characteristics of penicillin G. Thus, we combined data from a wide range of weights and ages by adding them as covariates in order to illustrate their relationships with the basic PK parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Ranheim et al reported that the clearance of penicillin was lower in 1-week-old piglets than in adult pigs (7,51). Musser et al found that the volume of distribution at steady state (V ss ) of the calf was significantly higher than that of adult cattle (5,30). The use of adult data only may not be able to describe all of the PK characteristics of penicillin G. Thus, we combined data from a wide range of weights and ages by adding them as covariates in order to illustrate their relationships with the basic PK parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Although most changes in PK seem to occur between newborn pre-ruminant and ruminating stages [43], [44], it is possible that age-related PK changes exist between calves and adult cattle, as observed in the human population [45]. Furthermore, PK parameters may be influenced by gender [46], physiological status [47], breed of cattle [48], or indeed the species (i.e. Bos taurus versus Bos indicus ).…”
Section: Discussionmentioning
confidence: 99%
“…The other kinetic parameters of sodium penicillin G were similar to cattle following i.v. administration (Soback et al ., 1987; Volner et al ., 1987; Bengtsson et al ., 1997) and displayed the typical characteristics of the penicillin family of antibiotics. These characteristics include a rapid distribution phase, short half‐life of elimination, and Vd SS indicative of distribution to the vascular and the extracellular fluid (Riviere et al ., 1991).…”
Section: Discussionmentioning
confidence: 99%